Kinetic Studies in the Mechanism of Oxidation of Glycine by Chloramine-T in Micellar System - Katre, Y.R.; Solanki, S.K.; Patil, Sangeeta; K. Joshi, Ghanat (Asian Journal of Chemistry, 2016)
The kinetic investigation of the oxidation of glycine by chloramine-T has been made in the presence of anionic surfactant i.e., sodium dodecyl sulphate (NaDS) at 313 K. The rate shows first order dependence on the oxidant but is fractional order with glycine. Increase in the concentration of NaDS inhibits the reaction rate. Various activation parameters have been calculated.